Why EU revenue matters: A case for an EU digital levy - Katerina Pantazatou (European Law Open)
This Article draws upon and connects three different developments: the ‘internationalisation’ of tax law and EU tax law, specifically; the increasing digitalisation of the economy, and the European Union’s need for more revenue to deal with the financial consequences of the COVID-19 pandemic and other policy priorities. It is explained why the taxation of data per se cannot be addressed at the global level at present and why the focus of research has to lie on the taxation of the different business models of the digital economy. In the absence of a global agreement as to how the digital economy should be taxed, the reaction of the European Union to such a fundamental undertaking remains uncertain and politically contingent on the outcomes of negotiation at the OECD level. Most particularly, on the so-called Pillar One agreement. A seemingly temporal solution to the taxation of the digital economy, the so-called DSTs (Digital Services Taxes) have been adopted by Member States of the EU and third countries, but their future remains uncertain. Amidst these developments, the EU has also looked for ways to increase its resources and to finance its post-Covid ambitious recovery plan. This need has led to a reconsideration of whether EU taxes could finance the EU budget (next to the Union’s own resources, which remain for the main part transfers from Member States). In this Article, I argue that beyond tax design considerations and potential constitutional impediments, the EU revenue side should be emphasised in the discussion. Therefore, I suggest that the Union should ensure that at least part of the revenue arising from digital taxation should be channeled to the supranational budget. Whether Pillar One gets adopted or not, the potential introduction of an EU digital levy, ideally by way of an EU tax, could help overcoming several shortcomings of the present tax status quo and could result in an increase of the resources at the disposal of the EU in a fashion compatible with the imperatives of democratic legitimacy.